Fusion zone microstructure evolution of fiber laser welded press-hardened steels. (August 2016) - Saha, Dulal Chandra; Biro, Elliot; Gerlich, Adrian P.; Zhou, Norman Y.
Abstract: Fusion zone microstructures of fiber laser welded Al-Si coated press-hardened steels at pre- and post-press-hardened conditions were analyzed using transmission electron microscopy (TEM). TEM and nanoindentation studies suggest that dislocation-free δ-ferrite phase formed in the weld metal (by ingress of the Al-Si surface coating into the fusion zone) exhibits lower nanohardness compared to α-ferrite transformed after press hardening. The nanoscale properties of δ-ferrite, α-ferrite, and martensite and their crystallographic orientation relationships are reported. Graphical abstract: